Eksplorasi Etnomatematika Pada Aksara Batak - Riski Ardian; Suparni (Universitas Gara Nusantara Padangsidimpuan, 2023)
Mathematical concepts can be used to explore mathematics in culture. The term used to associate mathematics and culture is ethnomathematics. Cultural elements such as traditional dances, traditional songs, customs, traditional languages, traditional games, traditional foods need to be preserved. One of them is Batak tribe. Batak tribe have traditional language and term of language is Batak script which was an important part of ancient times in writing documents, ancient manuscript, etc. The purpose of this research is to explore ethnomathematics in Batak scripts. This research was a qualitative research with an ethnographic approach. The results of this research found mathematical concepts, namely one dimensional geometry, intersecting lines, parallel lines, and acute angles. In addition, there is the concepts of geometric transformation, namely reflection on the x-axis and y-axis.